2015
DOI: 10.1099/jgv.0.000007
|View full text |Cite
|
Sign up to set email alerts
|

Phylodynamic evidence of the migration of turnip mosaic potyvirus from Europe to Australia and New Zealand

Abstract: Turnip mosaic virus (TuMV) is a potyvirus that is transmitted by aphids and infects a wide range of plant species. We investigated the evolution of this pathogen by collecting 32 isolates of TuMV, mostly from Brassicaceae plants, in Australia and New Zealand. We performed a variety of sequence-based phylogenetic and population genetic analyses of the complete genomic sequences and of three non-recombinogenic regions of those sequences. The substitution rates, divergence times and phylogeographical patterns of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
42
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(46 citation statements)
references
References 61 publications
2
42
0
Order By: Relevance
“…There have been such studies of plant viruses with single- and double-stranded DNA genomes, including begomoviruses and mastreviruses in the family Geminiviridae 5, 6 and cauliflower mosaic virus (CaMV) in the family Caulimoviridae 7 . Similar analyses have been conducted for plant viruses with RNA genomes, such as cucumber mosaic virus (CMV) in the family Bromoviridae 8 , and turnip mosaic virus (TuMV) 911 and potato virus Y 12 in the family Potyviridae . Genetic data for such studies are scarce for most viruses, except orthomyxoviruses and lentiviruses, and most have been done using partial genome sequences or using a single gene.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…There have been such studies of plant viruses with single- and double-stranded DNA genomes, including begomoviruses and mastreviruses in the family Geminiviridae 5, 6 and cauliflower mosaic virus (CaMV) in the family Caulimoviridae 7 . Similar analyses have been conducted for plant viruses with RNA genomes, such as cucumber mosaic virus (CMV) in the family Bromoviridae 8 , and turnip mosaic virus (TuMV) 911 and potato virus Y 12 in the family Potyviridae . Genetic data for such studies are scarce for most viruses, except orthomyxoviruses and lentiviruses, and most have been done using partial genome sequences or using a single gene.…”
Section: Introductionmentioning
confidence: 91%
“…These plants were developed from wild brassica plants by plant breeders during the expansion of agriculture. Previous studies have shown that this virus originated from wild orchids in Europe 10 and then spread among species of wild and domestic Brassicaceae plants, from the Mediterranean region, including South-east Europe, the Middle East and Central Asia 9, 19, 20 , to other parts of the world including East Asia 2123 , Oceania 11 and the Americas. There are two reports of TuMV from Middle Eastern countries 24, 25 .…”
Section: Introductionmentioning
confidence: 99%
“…An amino acid alignment revealed 10 amino acid changes from TuMV-QLD1a to TuMV-QLD1b. Both isolates share 96% identity with the AUST10 isolate (accession number AB989634), which was also collected in Queensland, Australia, in 1996 (3). Phylogenetic analysis places TuMV-QLD1a and TuMV-QLD1b in the basal-B group and subgroup basal-B2.…”
Section: Genome Announcementmentioning
confidence: 98%
“…This is considered to be the most variable group, as it emerged paraphyletic to the other lineages (5). This subgroup is most closely related to four German isolates, DEU7, AIIA, TIGD, and TIGA (accession numbers AB701695.1, AB701694.1, AB701735.1, and AB701734.1, respectively) and is thought to have been introduced into Australia and New Zealand via horticultural material (3). DEU7 and AIIA have 87% identity to both versions of TuMV-QLD1, while TIGD and TIGA have 86% identity.…”
Section: Genome Announcementmentioning
confidence: 99%
“…TuMV is a positive-strand RNA virus that infects not only Arabidopsis but also hundreds of other species in more than 40 plant families (Walsh and Jenner, 2002). It is considered to be one of the most damaging viruses for vegetable crops worldwide (Tomlinson, 1987;Nguyen et al, 2013;Yasaka et al, 2015) and is transmitted by the green peach aphid and many other aphid species in both natural and agricultural settings (Shattuck, 1992). Largely due to its ability to systemically infect Arabidopsis (Sánchez et al, 1998;Martín Martín et al, 1999), TuMV has become a model for potyvirus-host interactions (Walsh and Jenner, 2002).…”
mentioning
confidence: 99%